Pre-dispersal seed predators and fungi differ in their effect on Luehea seemannii capsule development, seed germination, and dormancy across two Panamanian forests - Pimonrat Tiansawat (2018)
© 2017 The Association for Tropical Biology and Conservation Pre-dispersal seed predation can greatly reduce crop size affecting recruitment success. In addition, non-fatal damage by seed predators may allow infection by fungi responsible for post-dispersal seed losses. The objectives of this study were (1) to quantify pre-dispersal seed predation and fungal infection in a Neotropical tree species, Luehea seemannii, that produces dehiscent fruits and wind-dispersed seeds, and (2) to link pre-dispersal effects on seed quality to seed survival in the soil. To examine how seed predators and fungi influence seed losses, mesh exclosures, fungicide, and the combination of both treatments were applied to separate branches in the canopy of trees in Gamboa and Parque Natural Metropolitano (PNM), Panama. To determine if treatments affect seed viability and survival in the soil, half of the seeds collected from each treatment were buried for 4 weeks in forest soils and subsequently allowed to germinate before and after the breaking of dormancy. Overall, 24 percent of developing fruit were lost to insect attack. In contrast, fungi infected only 3 percent of seeds at the pre-dispersal stage. For seeds germinated directly after collection, fungicide significantly increased germination in the wetter site (Gamboa) but decreased germination in the drier site (PNM). The pre-dispersal insect exclosure treatment increased the fraction of seeds that remained dormant after burial in the soil. This result suggests that exposure to insect predators may cause physical damage to seeds that results in the loss of physical dormancy but does not necessarily increase the susceptibility of seeds to pathogen attack in the soil.